Formulation and quality characterization of flat bread from pearl millet blended composite flour - KAUR, PARAMJOT; SOOD, MONIKA; BANDRAL, JULIE D; KAUL, RAJKUMARI (The Indian Journal of Agricultural Sciences, 2017)
In the present study, pearl millet flour was blended with refined wheat flour and soy protein isolates for the development of flat bread. The developed products were stored for 18 days to ascertain the changes in physico-chemical and sensory characteristics. In case of flat bread, water absorption of composite flour showed a significant increase with the incorporation of pearl millet flour, whereas gluten content and falling number decreased with the increase in percentage of pearl millet flour. Although, T6 (40:50:10:: pearl millet flour: refined wheat flour: soy protein isolates in flat bread) treatment recorded highest water absorption, but gluten and falling number were highest in treatment T1 (00:100:00:: pearl millet flour: refined wheat flour: soy protein isolates). The highest moisture, crude fat, crude fibre and ash content of 26.31, 4.00, 2.81 and 2.53 per cent were recorded in T6 (40:50:10:: pearl millet flour: refined wheat flour: soy protein isolates). However, T2 (00:90:10:: pearl millet flour: refined wheat flour: soy protein isolates) recorded highest value of crude protein (16.58 per cent). Sensory evaluation of flat bread revealed that T1 (00:100:00:: pearl millet flour: refined wheat flour: soy protein isolates) recorded highest mean score for overall acceptability (8.42), whereas T6 (40:50:10:: pearl millet flour: refined wheat flour: soy protein isolates) recorded lowest mean scores for overall acceptability (6.53).